1973
DOI: 10.1007/bf00015355
|View full text |Cite
|
Sign up to set email alerts
|

Diatom Succession and Interaction in Littoral Periphyton and Plankton

Abstract: Periphyton and plankton samples were collected at four littoral stations in a relatively shallow, eutrophic lake (Elk Lake, B .C ., Canada) over a six month period from August 1967 to January 1968 . The most abundant planktonic diatoms demonstrated a pattern of seasonal succession typical of temperate lakes, and all were present in the periphyton . This pattern was identical at all stations : Fragilaria crotonensis was dominant from August to October, Asterionella formosa in November and December, and Melosira… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

1973
1973
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(19 citation statements)
references
References 34 publications
0
19
0
Order By: Relevance
“…The existence of density-dependent factors in nature is indicated by the negative correlations between the species diversity and the density of benthic diatom populations (Brown and Austin, 1973;Colijn and Dijkema, 1981;Admiraal et al, 1984). Another indication is provided by the similarity between the population density in our step-wise diluted cultures and that in well developed natural communities.…”
Section: Effects Of Interspecific Competition On the Distribution Of mentioning
confidence: 79%
“…The existence of density-dependent factors in nature is indicated by the negative correlations between the species diversity and the density of benthic diatom populations (Brown and Austin, 1973;Colijn and Dijkema, 1981;Admiraal et al, 1984). Another indication is provided by the similarity between the population density in our step-wise diluted cultures and that in well developed natural communities.…”
Section: Effects Of Interspecific Competition On the Distribution Of mentioning
confidence: 79%
“…Brown & Austin (1973) found that the density of C. placentula on glass slides was correlated with the density of Achnanthes minutissima such that increases in the proportion of one corresponded to decreases in the other. Patrick (1978) described a similar relationship between C. placentula and A. lanceolata while TUchmann & Blinn (1979) have reported a relationship between the relative proportions of C. placentula and Amphora coffeiformis (Ag.…”
Section: Discussionmentioning
confidence: 91%
“…A survey of the literature has indicated a preference for slow moving water in lotic habitats (Jones, 1978), horizontal positioning (Godward, 1934), moderate specific conductance and alkalinity (Patrick & Reimer, 1966;Higashi et al, 1981;Tuchmann & Blinn, 1979), moderate water temperature (Hickman & Klarer, 1974;Tuchmann & Blinn, 1979;Hickman, 1982), high nitrate concentration (Patrick, 1978;Fairchild et al, 1985), high phosphate concentration (Fairchild et aL, 1985), high potassium, calcium and zinc concentrations (Podzorski, 1984), and low light intensity (Hickman & Klarer, 1974;Hickman, 1982;Jenkerson & Hickman, 1983). Other factors which may be related to high Cocconeis density include reduced susceptibility to grazing pressure (Patrick, 1970;Kesler, 1981), extended colonization period (Kesler, 1981), increased substratum age (Siver, 1978;Rogers & Breen, 1981) and mid-late summer season (Brown & Austin, 1973;Kesler, 1981;Hickman, 1982). Some of these conclusions have undoubtedly arisen from subjective interpretations of assumed cause and effect relationships between observed periodicity and environmental factors.…”
Section: Discussionmentioning
confidence: 98%
“…Brown & Austin (1973) found Cocconeis placentula Ehr. to be dominant on glass slides placed in the littoral region of a lake.…”
Section: Discussionmentioning
confidence: 99%